Islamic Religious Education Based on Religious Intersubjectivity: Philosophical Perspectives and Phenomenology of Religion - Abdullah, M. Amin (Jurnal Pendidikan Agama Islam, 2022)
Purpose – This article discusses the idea of Islamic Religious Education based on religious intersubjectivity. Design/methods/approach – This paper presents the idea of Islamic Religious Education based on religious intersubjectivity with a philosophical perspective or approach and religious phenomenology. The philosophical approach is to delineate and discuss three varieties of new paradigm for religion, namely subjective, objective, and intersubjective belief. Meanwhile, the religious phenomenology approach is used to develop an "intersubjective" religious area. Intersubjective diversity is an area of human religiosity that marries and engages in intense and sincere deep dialogue between the links of subjective and objective self-awareness of human which are in opposition to each other. Findings – The formulation of this IRE model – based on the intersubjectivity of religion – must consider the following points: 1) Intelligent sorting of common patterns and unique patterns in history of religions and religious thoughts; (2) Epoche, which refers to the ability of a person or group to sincerely and purely set-aside the statements that are undermining, devaluing, demeaning, infidelizing, apostatizing, or hurtful to other groups in any form; (3) Eidetic vision, which is the search for the basic construction, core, substance or the deepest essence of human religiosity; (4) the historicity of religion; (5) Verstehen, which constitutes an effort to understand the essence of other religions earnestly and genuinely; (6) Compassion and harmony; (7) Inclusive-partnership and dialogical approach; and (8) Enlightening new religious thoughts, mentalities, and attitudes (al-aql al-Jadid al-istitla'). Originality/value – Seeing the important meaning of religious intersubjectivity, this religious model is very appropriate if applied in Islamic Religious Education (PAI) learning.